Physico-Chemical and Structural Characterization of Cellulose Nanocrystals Obtained by Two Drying Methods: Freeze-Drying and Spray-Drying - Melo-Hurtado, F; Caballero-Alvial, L; Matiacevich, S (Elsevier B.V., 2023)
This study evaluated the physical-chemical properties and structure of cellulose nanocrystals (CNC) produced from pine cellulose pulp, and dried by two different methods: Spray-Drying (SD) or Freeze-Drying (FD). After drying, CNC were characterized in terms of size, z-potential, elemental analysis, conductometric titration, crystallinity and thermogravimetry. Complementary, analysis by force microscopy, dynamic sorption and infrared spectroscopy were carried out. Results showed that different drying methods did not produce significant differences in zeta potential, crystallinity and degradation temperature. However, CNC dried by FD showed smaller size but higher aspect ratio, and higher sulfur content, which would explain the significant higher sorption observed in CNC-FD at relative humidity higher than 80%. Drying method does not influence the formation or modification of cellulose bonds as FTIR suggested. Our study suggests that how CNC is dried will influence the CNC s structure and will modify some of their physico-chemical properties. This information is relevant since it can be used as an input for the scale-up processing of CNC and would define the performance in some of their technological applications. © 2023 Elsevier Ltd